The Importance of Green Brand Knowledge to Purchase Intention - Purba, Roberto Roy; Simanjuntak, Owen De Pinto; Tambunan, Elisabet; Rahmat, Muhammad; Tirtayasa, Satria (Journal of International Conference Proceedings, 2025)
This research aims to determine the influence of green brand knowledge and environmental concern on green purchase intention among consumers who use the Shopee application in the city of Medan. This type of research is descriptive quantitative. The population in this study were customers who used the Shopee application with the research sample using the Lemeshow formula, namely 96 respondents using the Sample Random Sampling technique. The data analysis methods used are Instrument Test, Classic Assumption Test, Multiple Linear Regression Test and Hypothesis Test using the SPSS Version 26 for Windows program. The research results show that green brand knowledge has a positive and significant effect on green purchase intention. Environmental concern has a positive and significant effect on green purchase intention. green brand knowledge and environmental concern simultaneously have a positive and significant effect on green purchase intention.